Optimal placement of multi-period-based switched capacitor in radial distribution systems. (March 2020) - Sadeghian, Omid; Oshnoei, Arman; Kheradmandi, Morteza; Mohammadi-Ivatloo, Behnam
Abstract: This paper proposes a methodology for optimal allocation of multi-period-based switchable capacitor in radial distribution systems to minimize the energy loss and improve the voltage profile. In the proposed methodology, each monthly typical day is divided to numerous time segments under a so-called number of segments (NOS) factor. Several possible values of NOS are evaluated to seek its impact on system's yearly loss. In the optimization process, by considering a common value of NOS, an optimal candidate bus for locating capacitor is obtained while the capacitor step is optimized in each segment. To speed up the solving process, a technical constraint is offered to ignore the non-important states for capacitor size evaluation. Moreover, two methods for load flow calculations including the direct load flow and backward/forward sweep methods are investigated. The proposed methodology is applied to IEEE 10-bus, 33-bus, 69-bus, and 85-bus systems, and thereby relevant conclusions are drawn.